Manajemen Koleksi di Museum Sri Baduga sebagai Upaya Pelestarian Budaya - Maulida, Lina Tsamrotul; Anwar, Rully Khairul; Rukmana, Evi Nursanti (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2025)
Museums play a crucial role in preserving cultural heritage through systematic collection management. As a repository for various historical collections from West Java, Museum Sri Baduga must ensure these collections remain accessible for future generations as part of its cultural preservation efforts. This research aims to explore collection management at Museum Sri Baduga as a part of cultural preservation efforts analyzing current practices, challenges, and innovations. This research uses a descriptive qualitative method. The research findings indicate that collection management practices at Museum Sri Baduga include the acquisition, documentation, classification, preservation, and digitalization of collections. Various challenges, such as limited human resources, insufficient operational budgets, and inadequate infrastructure, hinder optimal collection management. Nevertheless, Museum Sri Baduga continues to attract visitors, demonstrating a strong public interest in cultural preservation. The introduction of various innovations, including digital multimedia displays and the Museum Sri Baduga application, aligns with advancements in information delivery technology. This research concludes that Museum Sri Baduga has successfully undertaken cultural preservation efforts, characterized by systematic collection management despite the challenges encountered and the innovations implemented.